Prosecution and criticism of the right to maintenance regulation - Cornejo Fava, Teresa (1972)
This paper focuses on the right to maintenance regulations. Firstly, the article addresses the constitutional development in the right to maintenance matters; secondly, the author analyzes the contradictions present in the legal system in this matter and, finally, the deficiencies in the regulation are studied. Likewise, with respect to the problems evidenced in Peruvian right to maintenance, the author offers her position on the mechanisms of immediate action (normative modifications) and mediate action (analysis of the system). End the paper by presenting a critical judgment on the institutions, procedural frameworks and content of the current regulation.